(untitled) - Knystautas, Emile (London, 2005)
Engineering Thin Films and Nanostructures with Ion Beams first focuses on the mechanisms of individual ion impacts upon their substrates. It addresses current challenges in building equipment needed to produce nanostructures in an industrial setting and examines the combination of ion-beam techniques, delineates the fabrication of nanopillars, nanoflowers, and interconnected nanochannels in three dimensions by using atomic shadowing techniques, and describes the production of nanopores of varying dimensions in polymer films alloys and superconductors using ion-beam irradiation. The last chapter shows how fingerprints can be made more reliable as forensic evidence by recoil-mixing them into the substrate using ion beams.
Keywords: Thin films,Nanostructures,Lon bombardment; Industrial applications